Analysis of the Development of the Human Development Index Kepahiang Regency 2017-2021 - Yustanti, Nirta Vera; Ariska, Yesi Indian (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study is to provide an overview of the development of human development of Kepahiang Regency in the last five years, namely from 2017 to 2021. It is expected to provide additional information that can help the Kepahiang Regency government in making decisions on what programs can be implemented in Kepahiang Regency to realize a prosperous society in all aspects. The data used was sourced from skunder data obtained from the website of the Central Statistics Agency (BPS) Kepahiang Regency. The data includes population, education and economic data. Data collection in this study through documentation methods. Overall, the Human Development Index of Kepahiang Regency increased from 2017 to 2021. The HDI value of Kepahiang Regency in 2021 was included in the medium welfare category in 2017 with a value of 60.66 and until 2021 it was also in the medium category with its HDI value of 68.62.